WIG craft and ekranoplan ground effect craft technology - Yun, Liang; Bliault, Alan; Doo, Johnny (Springer, 2010)
WIGs (Wing in Ground) are advanced hybrid air cushion crafts that offer a combination of speed, fuel efficiency, and ride smoothness. This book provides a comprehensive overview of the design, development and building of these vessels.